GWAS and transcriptome analysis reveal key loci associated with drought tolerance in soybean: GWAS and transcriptome analysis reveal key loci associated with drought tolerance in soybean - MILIND B RATNAPARKHE; GYANESH K SATPUTE; RISHIRAJ RAGHUVANSHI; SUBHASH CHANDRA; RUCHA KAVISHWAR; DIPENDRA SINGH; S NISHTHA; RUCHI SHROTI; VIRAJ KAMLE; GIRIRAJ KUMAWAT; SANJAY GUPTA; LAXMAN SINGH RAJPOOT; et al. (Journal of Oilseeds Research, 2023)
Genome-wide association and gene expression studies were conducted to identify key genes and markers associated with drought tolerance. GWAS panel consisting around 300 diverse soybean accessions were phenotyped for morpho-physiological traits under control and drought stress condition for three years during 2019-2021. Genotyping by Sequencing (GBS) of GWAS panel identified 66300 SNPs distributed over all the 20 chromosomes and were used for association analysis. GWAS analysis revealed closely located significant SNPs on chromosome 4 (50500762, 52098616 and 53008801) and chromosome 16 (32371663, 33082976 and 33283177). Key candidate genes related to MYB family, cell signaling gene (GPCR), salicylic acid synthesis, oxidative stress, auxin and ABA synthesis pathway were identified. Further few tolerant and susceptible haplotypes were also identified for real-time based expression analysis under drought stress condition.